GAMBARAN TINGKAT KECEMASAN KELUARGA PASIEN SKIZOFRENIA - Aprilia Rizky Arifiani; Maryana; Sarka Ade Susana (LPPM STIKES NOTOKUSUMO YOGYAKARTA, 2017)
Background: Schizophrenia is a brain disease that resulted in persistent and serious psychotic behavior, concrete thinking, and difficulty in information processing, interpersonal relationships as well as difficulties in solving problems. The circumstances giving its own emotional distress, emotional level that arise as a reaction to the stressor may vary, one of anxiety. The family with family member suffering from schizophrenia often feel anxiety in the face of a family member suffering from schizophrenia. Objective: The purpose of this research is to determine the level of anxiety the family of schizophrenia patients in Puskesmas Gamping I Sleman 2015. Method: This research is descriptive quantitative. The sampling technique used is consecutive sampling with 41 respondents. Data obtained from the questionnaires about anxiety response. Results: The results showed that most respondents (80.49%) had mild anxiety and a small proportion of respondents (19.51%) who experienced anxiety being counted and no respondents who experienced severe anxiety and panic. Conclusion: it can be concluded that the majority of families with a family member suffering from schizophrenia have mild anxiety.